2010
DOI: 10.1086/649557
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to Bacterial Infection: Difference between Species Could Be Due to Proteins in Serum

Abstract: Vertebrates vary in resistance and resilience to infectious diseases, and the mechanisms regulating the trade-off between these two often opposing protective processes are not well understood. Variability in the sensitivity of species to induction of damaging inflammation in response to equivalent pathogen loads (resilience) complicates the use of animal models that reflect human disease. We found that induction of pro-inflammatory cytokines from macrophages in response to inflammatory stimuli in vitro is regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
182
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(185 citation statements)
references
References 37 publications
(37 reference statements)
1
182
0
2
Order By: Relevance
“…Recent articles have highlighted tradeoffs that species make to balance often opposing evolutionary strategies for resistance vs. tolerance or resilience to infection (26,27). Relative to the human response, mice are highly resilient to inflammatory challenge (28,29). For example, the lethal dose of endotoxin is 5-25 mg/kg for most strains of mice, whereas a dose that is 1,000,000-fold less (30 ng/kg) has been reported to cause shock in humans (30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent articles have highlighted tradeoffs that species make to balance often opposing evolutionary strategies for resistance vs. tolerance or resilience to infection (26,27). Relative to the human response, mice are highly resilient to inflammatory challenge (28,29). For example, the lethal dose of endotoxin is 5-25 mg/kg for most strains of mice, whereas a dose that is 1,000,000-fold less (30 ng/kg) has been reported to cause shock in humans (30).…”
Section: Discussionmentioning
confidence: 99%
“…Most parameters of human NK cells have been acquired from cells derived from the blood compartment, whereas murine NK cells are mostly derived from spleen. It is interesting to note that the blood environment in mice and humans are greatly different, with murine plasma favoring the resilience of mice to bacterial infection (27).…”
Section: Antibacterial Innate Immunitymentioning
confidence: 99%
“…We have recently shown that gnotobiotic IL-10 −/− mice generated by broad-spectrum antibiotic treatment are excellently suited as C. jejuni infection model to study host-pathogen interactions in vivo [10][11][12]. It is well known that rodents are 1000 times more resistant to Toll-like receptor-4 agonists such as lipopolysaccharide (LPS) and lipooligosacharide (LOS) than humans [13]. In addition, IL-10 −/− mice are much more sensitive to LPS and LOS as compared to wildtype mice [10].…”
Section: Introductionmentioning
confidence: 99%